Pemanfaatan Teknologi Informasi sebagai Media Pembelajaran - Rusdi, Muhammad (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2019)
This paper aims to describe the use of information technology as a medium in learning, this is useful because technology is expected to improve student learning outcomes and the quality of individual students in the use of technology that is more effective and useful. This study was made using the analysis of documents and articles. We will start with the definition of information technology. First, we will also discuss the definition of information technology, which will be analyzed through several articles and journals. The results of the study show that computers are used in the classroom to teach basic skills and provide computer knowledge according to the curriculum. For example, word processing is used to improve students' writing skills. Computers are also widely used to convey material that requires motion, images, text, and color. All these facilities are on the computer and all these facilities can be used to visualize abstract concepts in mathematics into concrete. However, although the use of computers can improve student achievement, computers cannot replace the role of the teacher as a whole.